The Country House (with Designs) - Châteauneuf, Alexis de, 1799-1853; Eastlake, Charles Lock, Sir, 1793-1865; Fox, Mary, Lady, 1798-1864 (Salt Lake City, UT : Project Gutenberg, 2013)
"The Country House (with Designs)" edited by Lady Mary Fox is a collection of essays and letters on architectural principles and designs, written in the mid-19th century. The work aims to explore various domestic architectural styles and provides considerations for building a new house. The key figures mentioned include Monsieur De Chateauneuf, who discusses styles suitable for domestic architecture, and Mr. Eastlake, who contributes insights on interior decoration. The opening of the book introduces the motivations behind its creation, highlighting letters exchanged between a builder contemplating designing a new house and an architect offering detailed advice on style, site selection, and construction materials. The initial correspondence outlines the builder's specific desires for the house's layout and aesthetic while emphasizing the importance of the surrounding landscape and the need for a home that is both beautiful and functional. The letters promise a rich discussion on architecture, with references to various styles that underscore the contributors' artistic and practical concerns. (This is an automatically generated summary.)
Release date is 2013-01-05
E-text prepared by Clarity, Sandra Eder, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive/American Libraries (http://archive.org/details/americana)
Keywords: Architecture, Domestic -- England; Architecture -- England -- History -- 19th century; Country homes -- England